Experimental Evaluation of Through-Wall Detection Using an UWB Radar - Marcelo B. Perotoni; Leandro A. da Silva; Vinicius Silva (Journal of Microwaves, Optoelectronics and Electromagnetic Applications, 2024)
Abstract This paper discusses the through-wall detection of targets behind walls using an ultra-wideband radar operating in the 2 to 15 GHz frequency range. Tests were conducted to verify its use with static and moving targets. Two real-world cases were tested: a laboratory with students sitting on benches, and an adult person standing behind a door. A fast method, based on the standard deviation, was used to transform the time-domain data matrix into a simpler waveform. This method has the potential to quickly detect the presence of human targets behind physical obstacles.